PROPERTY RELATIONS IN CINEMATOGRAPHY: EVALUATION, EVOLUTION, MANAGEMENT - M. I. Pankratova (Вестник университета)
The process of gradual reform of property relations in cinematography in order to transition to a competitive market has been considered. The possible consequences of a reduction in the public sector in this area of activity have been analysed in detail. As a part of the research, the development of the film industry under the influence of a global global challenge-the spread of a new coronavirus infection (COVID-2019) has been reviewed also. In this regard, a hypothesis about the need for transition to extrabudgetary financing of the film business, has been formulated and proved. The influence of COVID-2019 on other sectors of the cultural sphere (museum, library, theater and others) has been analysed. The study was based on the regulatory legal acts of the Russian Federation, industry analytics of the Federal Fund for Social and Economic Support of Domestic Cinematography.